2018
DOI: 10.1002/bmc.4165
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of etonogestrel and ethinyl estradiol in human plasma by UPLC‐MS/MS and its pharmacokinetic study

Abstract: A selective, sensitive and rapid ultra-performance liquid chromatography tandem mass spectrometry method was developed and validated for the simultaneous determination of etonogestrel (ENG) and ethinyl estradiol (EE) in human plasma. The analytes and their deuterated internal standards, ENG-d7 and EE-d4, were extracted from plasma samples by solid-phase extraction on HyperSep™ Retain PEP cartridges. The chromatographic analysis was performed on an Acquity UPLC HSS Cyano column, 100 Å (50 × 2.1 mm, 1.8 μm), col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although solid phase extraction (SPE) was implemented in earlier reports [33], it was not given priority as it was very costly. The nonpolar nature of the EE makes it an ideal candidate for liquid-liquid extraction (LLE) that is cost effective compared with SPE and could produce not only purified, but also concentrated, samples for spectral analysis.…”
Section: Optimization Of the Extraction Protocolmentioning
confidence: 99%
“…Although solid phase extraction (SPE) was implemented in earlier reports [33], it was not given priority as it was very costly. The nonpolar nature of the EE makes it an ideal candidate for liquid-liquid extraction (LLE) that is cost effective compared with SPE and could produce not only purified, but also concentrated, samples for spectral analysis.…”
Section: Optimization Of the Extraction Protocolmentioning
confidence: 99%
“…The literature review conducted on ethinyl estradiol and etonogestrel indicated that only derivative spectroscopic analysis has been reported [12]. However, for ethinyl estradiol with other drugs, derivative spectroscopy [13], UPLC-MS [14][15][16], for fixed combination dosage form of Nuvaring and with other com-binational drugs on HPLC [17][18][19] are reported. To the best of our knowledge, there is no published data about the use of HPLC-MS for the analysis of the fixed combination of ethinyl estradiol and etonogestrel.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that only few research studies are available on the simultaneous determination of EDA and EE in different formulations (Amin & Hassenbach, 1979; Babják, Balogh, Gazdag, & Görög, 2002; Carignan, Lodge, & Skakum, 1982; Gluck & Shek, 1980; Havlíková, Nováková, Matysová, Šícha, & Solich, 2006; Koneru, Kimbahune, Mubeen, Lalitha, & Chakraborty, 2015; Kotra, Ramisetti, & Konidala, 2017; Maziarz, 2013; Nair et al, 2018; Patel, Rathod, & Patel, 2013; Prasad, Reddy, Prasad, & Mukkanti, 2001; Qi Gui & Nieuweboer, 1989; Strusiak, Hoogerheide, & Gardner, 1982; Suhendi, 2016; Summers & Fountain, 2013; Yamada, Kuwahara, Takamatsu, & Hayase, 2000; Zorica, 2006). This paper describes a sensitive and straightforward high‐performance chromatographic method for determining EDA and EE in tablets.…”
Section: Introductionmentioning
confidence: 99%